2017
DOI: 10.1186/s13690-017-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Availability of adequately iodized in Northwest Ethiopia: a cross-sectional study

Abstract: BackgroundUniversal salt iodization is the most cost-effective, safe and sustainable strategy to eliminate iodine deficiency disorders. However, little is known about the availability of adequately iodized salt in the northwestern part of Ethiopia. Thus, the aim of this study was to assess the availability of adequately iodized salt at the household level and associated factors in Dabat District, northwest Ethiopia.MethodsA community-based cross-sectional study was conducted from February 21 to March 31, 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
(19 reference statements)
5
24
4
Order By: Relevance
“…This warrants assessment of salt iodine contents using a quantitative marker such as a titration method. This finding is consistent with other study in the same population which reported 33.2% households used adequately iodised salt post fortification [15]. Higher proportion of inadequate salt iodine content among households in the study area indicates a possibility of fluctuations in iodised salt supply in the community or availability of non-iodised salt in the local market or poor utilization of iodised salt including use of open containers to store salt, exposing the salt to sunlight and storage of salt for long period of time at the household level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This warrants assessment of salt iodine contents using a quantitative marker such as a titration method. This finding is consistent with other study in the same population which reported 33.2% households used adequately iodised salt post fortification [15]. Higher proportion of inadequate salt iodine content among households in the study area indicates a possibility of fluctuations in iodised salt supply in the community or availability of non-iodised salt in the local market or poor utilization of iodised salt including use of open containers to store salt, exposing the salt to sunlight and storage of salt for long period of time at the household level.…”
Section: Discussionsupporting
confidence: 93%
“…the 2016 Ethiopian Demographic and Health Survey reported 89.3% households used iodised salt [13]. The proportion of households using adequately iodized salt after introduction of the USI program were 29.7% in Lay Armachiho district [14], 33.2% in Dabat district [15], 28.9% in Gondar town [16], and 26.2% in Shebe Senbo district [17]. High prevalence of goiter [14,[17][18][19][20][21] and median UIC < 100 μg/l [17,19,[21][22][23] was also reported across the country pre-and post-mandatory salt iodization in 2011.…”
Section: Introductionmentioning
confidence: 99%
“…18 In Dabat and Laelay Maychew districts of Northern Ethiopia similar adequately iodised salt utilisation was observed. 5,19 Levels of iodine in salt can be affected by many factors. In the current study the age of the respondents, their educational status and the place where salt is stored showed statistically significant associations with salt being iodised.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Dabat and Laelay Maychew districts of Northern Ethiopia those who had attended formal education were more likely to have access to adequately iodised salt. 5,19 In Ghana too iodised salt is used more by those respondents who attended formal education. In both Ghana and the current study salt that has been purchased from the marketplace had a lower quantity of iodine compared with salt purchased from a shop.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are known to affect iodized salt utilization. Most importantly, being female, married (19,20), having knowledge on IDD and iodized salt (19,(21)(22)(23)(24)(25), higher educational status (24,(26)(27)(28), and higher monthly income (26,27,29) are signi cantly associated with iodized salt utilization.…”
Section: Introductionmentioning
confidence: 99%